Tanggung Jawab Hukum Perusahaan terhadap Kesehatan dan Keselamatan Kerja Karyawan - Vressilia Witama; Dinda Ayu Arini Chaniago; Irpan Mauliandi Damanik; M Rangga Syahputra Saragih; Siti Salmiah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Occupational health and safety (OHS) is a crucial aspect that must be addressed by companies to protect employees from the risks of accidents and health issues in the workplace. This study aims to examine the legal responsibilities of companies regarding the implementation of OHS and to explore the challenges they face in fulfilling these obligations. The research method used is descriptive qualitative, by collecting data through literature studies and in-depth interviews with relevant parties. The results show that companies generally have a good understanding of their legal obligations related to OHS, which is reflected in policies and routine training provided to employees. However, the implementation still faces several obstacles such as limited facilities, lack of supervision, and low work discipline, all of which affect the effectiveness of OHS practices. Legally, the regulations governing OHS are adequate, but law enforcement and monitoring must be improved to ensure that companies fulfill their responsibilities optimally. Furthermore, the social and ethical dimensions are also essential in building a safety culture that supports employee well-being and business continuity. In conclusion, the legal responsibility of companies for OHS must be implemented comprehensively and sustainably to ensure a safe and productive work environment.